Mapping the pathways to health sciences librarianship: reflections and future implications from an immersion session. - Laynor, Gregory; Tagge, Natalie; Magro, Juliana; De Armond, Megan; Rau, Renée A.; Vardell, Emily (Journal of the Medical Library Association, 2023)
Objective: Many health sciences librarians enter the profession without specific health sciences training. Some LIS programs have health sciences courses or tracks, but health sciences training within an LIS program is only one path to entering health sciences librarianship. To develop a map of pathways into health sciences librarianship, an immersion session at the Medical Library Association conference in 2022 asked health sciences librarians to share how they entered the profession. Methods: The immersion session was structured in three parts: facilitator introductions, small group discussions, and a whole group summary discussion. Guided by questions from the facilitators, small groups discussed what pathways currently exist, how to promote existing pathways, what new pathways should be created, and how to develop and promote pathways that make the profession more equitable, diverse, and inclusive. Results: Through in-the-moment thematic analysis of the small group discussions, the following emerged as key pathways: library school education; internships and practica; the Library and Information Science (LIS) pipeline; on-thejob training; mentoring; self-teaching/hands-on learning; and continuing education. Themes of equity, diversity, and inclusion arose throughout the session, especially in the concluding whole group discussion. Conclusion: Small group discussions in a conference immersion session showed the value of community building in a profession that has multiple pathways for entrance, highlighting the importance of unearthing hidden knowledge about avenues for exploring and enhancing career pathways. The article seeks to address barriers to entry into the profession and adds to the literature on strengthening the field of health sciences librarianship.